Penggunaan Model Pembelajaran Kontekstual terhadap Kemampuan Qira'ah Siswa SD Islam Al-Falah 2 Kota Jambi - Rahmi Auliya; Sahrizal Vahlepi; Anwar Sanusi; Sulhi Muhammad Daud Abdul Kadir (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to determine the effect of the use of the Contextual Teaching and Learning learning model on the Maharah qira’ah of students at Al-Falah 2 Islamic Elementary School in Jambi City. The background of this study is that it was found that most students do not have adequate skills in maharah qira’ah. This research uses a quantitative experimental method. The research design used in this research is a quasi-experimental design in the form of a nonequivalent control group design. Data were collected through observation, tests and documentation involving Arabic language teachers and fourth grade students. The results of this study indicate that the use of the CTL learning model has an impact on students' maharah qira'ah. This research is expected to provide tangible benefits for improving the quality of Arabic language learning, particularly in the aspect of maharah qira'ah.